COMPARISON OF BODY COMPOSITION ACCORDING TO AGE AND GENDER IN PATIENTS WITH CHRONIC KIDNEY DISEASE (CKD). - Aleksandra Rymarz; Katarzyna Szamotulska; Małgorzata Gomółka; Stanisław Niemczyk (The Korean Society of Nephrology, 2012)
The aim of the study was to compare: Body Cell Mass Index (BCMI), Lean Tissue Index (LTI), Fat Tissue Index (FTI) measured by multifrequency bioimpedance spectroscopy (Body Composition Monitor-FMC) according to age and gender in patients with CKD stage 4-5 (NKF) without dialysis treatment and in hemodialysis patients (HD). We included 45 adult patients (pts) with CKD and eGFR < 30 ml/min not treated with dialysis - predialysis group (26 male, age: 59,7 ±16,8) and 39 adults treated with HD three times a week, for more than three months (26 male, age: 59,8 ±16,0). We defined BCMI as Body Cell Mass divided by square body height and analogically LTI and FTI (kg/m2). In statistics analysis we used t-student test (SPSS v18). Predialysis BCMI LTI FTI BMI ≤ 59 y 8,0 ±1,6 14,4 ±2,4 12,5 ±5,4 27,7 ±5,5 ≥ 60 y 6,4 ±1,4 11,9 ±2,0 15,8 ±5,0 28,5 ±4,8 Females 6,0 ±1,2 11,3 ±1,8 17,2 ±6,3 28,5 ±6,1 Male 7,9 ±1,5 14,2 ±2,1 12,7 ±3,5 28,0 ±4,0 In predialysis pts mean BCMI and LTI were significantly lower in females and older whereas BMI did not differ significantly. Mean FTI was significantly higher in females (for all p < 0,05). Hemodial. BCMI LTI FTI BMI ≤ 59 y 7,2 ±1,7 13,2 ±2,5 10,3 ±7,0 24,0 ±5,3 ≥ 60 y 5,8 ±1,4 11,3 ±1,9 13,3 ±4,9 25,4 ±4,4 Females 6,4 ±1,4 12,0 ±1,9 11,5 ±4,8 24,0 ±4,4 Males 6,4 ±1,8 12,2 ±2,6 12,2 ±6,6 25,1 ±5,0 In hemodialysis patients no significant differences was observed in females and males in all BCMI, LTI, FTI and BMI. BCMI, LTI were significantly lower in older pts whereas BMI did not differ significantly (for all p < 0,05). In both groups BCMI and LTI decline in patients over 60 years whereas only in hemodialysis patients they do not differ in females and males. Analysis of body composition in patients with CKD is worth to be studied in large group of patients.